Investigation of corneal hydration and the impact of cross-linking therapy on water retention using Brillouin spectroscopy, Raman spectroscopy and polarization-sensitive optical coherence tomography - Rix, Jan; Steuer, Svea; Golde, Jonas; Husein, Fadi; Lochmann, Felix; Melcher, Steven; Steiner, Gerald; Galli, Roberta; Walther, Julia; Raiskup, Frederik; Khoramnia, Ramin; Herber, Robert (Frontiers in Bioengineering and Biotechnology, 2025)
Recently, Brillouin spectroscopy has been proposed as a promising non-invasive tool to evaluate corneal biomechanics, e.g., during corneal cross-linking (CXL) treatment. However, the impact of corneal hydration on the Brillouin shift hampers straightforward interpretation of the measurements, especially when judging on the success of the CXL procedure. Therefore, in this work, we first quantify the effect of corneal (de)hydration on the Brillouin shift revealing that reliable measurements are only possible under constant hydration conditions, which was subsequently achieved by immersing porcine eyes in solution and waiting until an equilibrium state was reached. Investigations showed that Brillouin spectroscopy evaluates the CXL effect mainly indirectly via reduced water uptake, while polarization-sensitive optical coherence tomography evaluates the CXL effect directly via changes in collagen fiber alignment and is therefore insensitive to corneal hydration. Raman spectroscopy is not indicating any alterations in the molecular structure revealing that new cross-links are not created due to the CXL procedure. Compared to large water retention in balanced salt solution, the missing water uptake in dextran-based (16%) solution hampers the evaluation of the CXL effect by Brillouin spectroscopy.